Bilinear and Bilateral Summation Formulae of Certain Polynomials in the Form of Operator Representations: Mumtaz Ahmad Khan, K.S. Nisar - Team, Support (Thai Journal of Mathematics, 2011)
Based on the technique used by Khan and Shukla [1] certain bilinear and bilateral summation formulae for various polynomials, whose Rodrigues or Rodrigues type formulae are known, have been obtained in terms of operational representations using derivatives and difference operators.The results obtained are believed to be new.